KAJIAN SIFAT FISIKA DAN KIMIA TANAH PADA LAHAN KELAPA SAWIT DENGAN BEBERAPA JENIS VEGETASI YANG TUMBUH DI KEBUN PTP NUSANTARA III TANAH RAJA (Study of Physical and Chemical Soil Characteristics in Oil Palm Plantation with Several Vegetations That Grow in - Leni Leni; Sumono Sumono; Nazif Ichwan (Universitas Sumatera Utara, 2017)
ABSTRACT Physical and chemical soil characteritic is an important factor for the growth of oil palm. This research was aimed to study physical and chemical soil characteritics on the oil palm with vegetation Mucuna bracteata, Nephrolepis biserrata, grass and without vegetation in Tanah Raja PTP Nusantara III. The observed parameters were soil texture, porosity, water content of field capasity, soil permeability, total Nitrogen, available soil Phosphate, and land Potassium exchange. The results showed that the soil type was ultisol with sandy clay loam texture and pH ranged from 4.95 to 5.29 (sour). The soil vegetations had porosity of 50.44 to 52.21% at a depth of 5 cm and 46.86 to 46.96% at a depth of 25 cm. The water content of field capacity was ranged from 32.12 to 38.98%. Permeability was ranged from 4.57 to 6.01 cm/h at a depth of 5 cm and 2.21 to 3.69 cm/h at a depth of 25 cm. N total was ranged from 0.11 to 0.12%. P available was ranged from 12.87 to 18.96 ppm. K exchange of land was ranged from 0.56 to 0.61 me/100g. The soil without vegetation had porosity of 46.91% at a depth of 5 cm and 45% at a depth of 25 cm. The water content of field capacity was 31.54%. Permeability was 2.86 cm/h at a depth of 5 cm and 1.84 cm/h at a depth of 25 cm. Total N was 0.09%. P available was 10.75 ppm. K exchange of land was 0.55 me/100g. Keyword: Soil physical and chemical, vegetation, oil palm plantation ABSTRAK Sifat fisika dan kimia tanah merupakan faktor penting bagi pertumbuhan kelapa sawit. Penelitian ini betujuan untuk mengkaji sifat fisika dan kimia tanah pada lahan kelapa sawit dengan vegetasi kacang-kacangan (Mucuna bracteata), paku harupat (Nephrolepis biserrata), rumput dan tanpa vegetasi di Kebun PTP Nusantara III Tanah Raja. Parameter yang diamati meliputi tekstur tanah, porositas, kadar air kapasitas lapang, permeabilitas tanah, N-total, P tersedia dan K tukar tanah. Hasil penelitian menunjukkan jenis tanah di daerah penelitian adalah ultisol bertekstur lempung liat berpasir dan pH berkisar 4,95-5,29 (masam). Tanah dengan vegetasi mempunyai porositas berkisar 50,44-52,21% pada kedalaman 5 cm dan 46,86-46,96% pada kedalaman 25 cm, kadar air kapasitas lapang berkisar 32,12-38,98%, permeabilitas berkisar 4,57-6,01 cm/jam pada kedalaman 5 cm dan 2,21-3,69 cm/jam pada kedalaman 25 cm, N-total berkisar 0,11-0,12%, P tersedia berkisar 12,87-18,96 ppm, K tukar tanah berkisar 0,56-0,61 me/100g. Tanah tanpa vegetasi mempunyai porositas 46,91% pada kedalaman 5 cm dan 45% pada kedalaman 25 cm, kadar air kapasitas lapang 31,54%, permeabilitas 2,86 cm/jam pada kedalaman 5 cm dan 1,84 cm/jam pada kedalaman 25 cm, N-total 0,09%, P tersedia 10,75 ppm, K tukar tanah 0,55 me/100g. Kata Kunci: Fisika dan kimia tanah, vegetasi, lahan kelapa sawit